Preparation of nanofiber core-spun yarn based on cellulose nanowhiskers/quaternary ammonium salts nanocomposites for efficient and durable antibacterial textiles. (December 2022) - Zheng, Huanli; Li, Xiang; Liu, Luyao; Bai, Chenguang; Liu, Baihe; Liao, Huanru; Yan, Mengmeng; Liu, Fan; Han, Pengju; Zhang, Hui; He, Jianxin
Abstract: Antibacterial fabrics are critical for the prevention of illness. Herein, we present a strategy for the preparation of a novel efficient and durable antibacterial nanofiber core-spun yarn (NCY) and antibacterial textile based on cellulose nanowhiskers (CNWs)/quaternary ammonium salts (QASs) composites for addressing the problems of easy shedding of antibacterial agents, unstable antibacterial effect, and triggering bacterial resistance in traditional antibacterial textiles. Through a facile coupling procedure, QAS and CNW are synthesized as CNW-QAS, which is a stable nanocomposite antibacterial agent. Based on a conjugated electrospinning device, CNW-QASs are firmly immobilized on the CNW-QAS/polyacrylonitrile (PAN) nanofiber shell layer by combining in situ doping with co-spinning to construct CNW-QAS/PAN NCY with efficient, fast and durable antibacterial properties. Its antibacterial rates against E. coli and S. aureus are both 99.99% even after multiple washes and long-term storage. In addition, the antibacterial yarn possesses a stress of 42.25 MPa and strain of 96.08%, providing excellent mechanical properties and flexibility. The exceptional performance makes CNW-QAS/PAN NCY a promising candidate for next generation antibacterial textiles. Graphical abstract: Image 1 Highlights: A novel stable, efficient and non-leaching nanocomposite antibacterial agent CNW-QAS is developed based on cellulose nanowhiskers. CNW-OAS is firmly embedded on the nanofibers by a combination of in situ doping and co-spinning to construct antibacterial yarns. The prepared yarns exhibit rapid, efficient, and durable antibacterial properties (99.99%), as well as enhance mechanical performance.